Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.11604/pamj.2015.20.246.5169
|View full text |Cite
|
Sign up to set email alerts
|

Etude du faible poids de naissance associé à l’âge maternel et la parité dans une population couple mère-enfant suivi à Lubumbashi

Abstract: IntroductionEvaluer l'influence de l’âge maternel et de la parité sur la naissance d'un faible poids de naissance (FPN) à Lubumbashi.MéthodesIl s'agit d'une étude basée sur une analyse documentaire des dossiers médicaux des accouchées enregistrées dans les maternités des 10 hôpitaux généraux de référence (HGR) de la ville de Lubumbashi en République Démocratique du Congo entre le 1er décembre 2013 et le 31 mars 2014. Ces accouchées ont été réparties en deux groupes, en fonction du poids de naissance de leurs e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 30 publications
(29 reference statements)
0
4
1
Order By: Relevance
“…This is high compared to the national rate according to Mali's latest Demographic and Health Survey (EDSM-VI 2018) which reported a rate of 15%[2]. The high frequencies in developing countries seem to be explained by the multiplicity of risk factors, in particular malnutrition, insufficient monitoring of pregnancy, malaria and repeated urogenital infections during pregnancy[6]. Our rate is high compared to TELLY's.…”
contrasting
confidence: 49%
See 1 more Smart Citation
“…This is high compared to the national rate according to Mali's latest Demographic and Health Survey (EDSM-VI 2018) which reported a rate of 15%[2]. The high frequencies in developing countries seem to be explained by the multiplicity of risk factors, in particular malnutrition, insufficient monitoring of pregnancy, malaria and repeated urogenital infections during pregnancy[6]. Our rate is high compared to TELLY's.…”
contrasting
confidence: 49%
“…They had a gestational age of 28 SA-33 SA with an average of 32.5 SA, the average weight was 1897 g with extremes [703 g -2490 g], hypothermia in 65.07% and the age at admission was D0 (78.94%) (Table 1). [6]. The disparity in LBW prevalence rates between areas could be explained by the place of study and the study population.…”
Section: Resultsmentioning
confidence: 99%
“…In fact, the authors' studies treated all women of childbearing age between 15 and 49 years, unlike ours, which only included women aged 20 and over. However, a maternal age of less than 20 years has been proved in the etiology of LBW [31][32][33][34]. These authors showed that the risk of giving birth to a LBW child is higher among women under the age of 20 years compared to other adult women.…”
Section: Discussionmentioning
confidence: 99%
“…Both tools were pre-tested by the investigator in a maternity hospital in Lomé. The dependent variable was the LBW of the newborn, de ned as a birth weight of less than 2500 grams [10][11][12]. In the mother, the variables collected were the number of doses of IPT-SP received during her last pregnancy, socio-demographic characteristics (age, level of education, marital status, occupation, area of residence) and clinical characteristics (parity, number of living children, number of Antenal Care (ANC) visits, number of IPT-SP doses taken).…”
Section: Data Collection and Toolsmentioning
confidence: 99%
“…Maternal malaria is responsible for more than 35% of low birth weight (LBW), one of the most important risk factors for infant mortality [9]. Indeed, LBW is de ned in a newborn as a birth weight below 2,500 g and is a public health problem [10][11][12]. To prevent maternal malaria, and reduce the incidence of LBW, the WHO has recommended since 2010 that all women should receive at least three doses of intermittent preventive treatment with Sulfadoxine Pyrimethamine (IPT-SP) after the rst trimester of pregnancy until delivery [13,14].…”
Section: Introductionmentioning
confidence: 99%